Sistem Aplikasi Mobile untuk Pengelolaan Pengingat Obat dan Jadwal Medis dengan Teknologi Notifikasi Cerdas - Hidayat, Taufik; Ikrimach, Ikrimach (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Patient adherence to medication schedules and medical consultations is one of the main challenges in the healthcare sector. Non-adherence to medication can lead to therapy failure, drug resistance, and increased healthcare costs. To address this issue, this study develops a Mobile-Based Health Management System designed to manage medical schedules and provide medication reminders through intelligent notifications. This system is built using Flutter for the user interface (frontend), Node.js for the backend, and MySQL for the database. The main feature of this system is the integrated automatic reminders for medication schedules and medical consultations, which can be customized according to user preferences. By utilizing notification technology, the system ensures that reminders are sent on time and accurately, supporting improved medication adherence. This research applies Black Box Testing to evaluate the system's functionality, resulting in 100% success in CRUD operations and 98% notification timeliness accuracy. The testing results demonstrate that the system works well in managing medical schedules and medication reminders, and significantly contributes to improving medication adherence. Additionally, the system makes it easier for users to manage their medical schedules more efficiently and is accessible via mobile devices. The developed system has the potential to be widely implemented as an integrated mobile-based health management platform, supporting the digital transformation in the healthcare sector.